Understanding the role of intrinsic motivations in information technology usage habit: evidence from instant messenger and search engine. (12th July 2011) - Song, Peijian; Zhang, Cheng
Drawing upon insights from the habit/automaticity perspective, the current study attempts to incorporate the intrinsic motivators of information technology usage habit and propose a research schema for understanding the antecedents of online service usage habits. The proposed model was empirically tested using 504 cross-sectional responses from actual users of instant messenger and search engine. The results suggest that individual satisfaction, perceived enjoyment and frequency of past behaviour positively influence the strength of usage habit. In addition, information technology type is found to moderate the effects of individual satisfaction and perceived enjoyment on usage habit: perceived enjoyment has a stronger effect on usage habit building for instant messenger users, while satisfaction has a stronger effect for search engine users. This research not only contributes to the important, yet relatively under explored subject of IS usage habits, but also shed light on the marketing promotion strategies for information technology in electronic markets.